Kekerabatan Orang Toraja Kristen-Islam Berdasarkan Nilai Kultural Tongkonan dan Falsafah Misa’ Kada Dipotuo, Pantan Kada Dipomate - Feky Markus (Program Pascasarjana UKIM, 2022)
This article discusses the harmonization of the kinship of the Christian-Muslim Toraja in the cultural values of Tongkonan, and the philosophy of misa 'kada dipotuo, pantan kada dipomate. The purpose of this study is to analyze the kinship relationship that is maintained and harmonious in Toraja. This research is qualitative research, with a phenomenological and historical approach. The author collects data through observation, interviews, and a literature review of the cultural context of the Toraja people's kinship. The central thesis of this article is the harmonization of the Christian-Muslim Toraja's kinship relations based on the richness of cultural values of tongkonan and the philosophical importance of the unity of the Toraja people through the motto misa’ kada dipotuo, pantan kada dipomate. Kinship based on the cultural values of the Toraja people contributes to building and maintaining the nation’s integrity.